ENGLISH - VIETNAMESE AERONAUTICAL ENGINEERING TEXTBOOK COVER DESIGNS: A CONTRASTIVE STUDY FROM THE THEORY OF MULTIMODAL DISCOURSE ANALYSIS - Tran, Hong Lam; Lam, Quang Dong (VNU Journal of Foreign Studies, 2025)
Abstract: This mixed-method study compares and contrasts Vietnamese and English aeronautical engineering textbook covers using Multimodal Discourse Analysis (MDA) by Kress and van Leeuwen’s (2006) visual grammar framework. By examining the cover designs through interactive meaning (social distance and perspective) and compositional meaning (information value, framing, and salience) across 25 covers per language, the study unveils similarities in the use of photographic distances for social relationships, predominance of subjective angle images, framing techniques, top-down layouts, and consistent title/author elements. However, differences arise in the book cover design choices based on the visual grammar framework. Vietnamese covers often depict impersonal distance via long shots, while English covers favour oblique angles, suggesting detachment. Vietnamese covers segregate images and text, whereas English covers integrate images as backgrounds. Vietnamese covers include more supplementary metadata like genre and audience. These differences highlight cultural, stylistic, and marketing influences across linguistic contexts, demonstrating that integrating multimodal and contrastive analyses deepens understanding of textbook covers as complex semiotic systems and informs the development of more effective, culturally relevant designs to enhance aeronautical engineering education.